2021
DOI: 10.1055/a-1482-6381
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Depsidones with Biological Interest

Abstract: Depsidones are some of the most abundant secondary metabolites produced by lichens. These compounds have aroused great pharmacological interest due to their activities as antioxidants, antimicrobial, and cytotoxic agents. Hence, this paper aims to provide up-to-date knowledge including an overview of the potential biological interest of lichen depsidones. So far, the most studied depsidones are fumarprotocetraric acid, lobaric acid, norstictic acid, physodic acid, salazinic acid, and stictic acid. Their pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 135 publications
0
15
0
Order By: Relevance
“…Thus, from the depsides group, atranorin shows antimicrobial, anti-proliferative, cytoprotective, anti-inflammatory, and antioxidant activities [ 26 ]; lecanoric acid has antimicrobial [ 27 ], anti-proliferative [ 28 ], and antioxidant [ 29 ] effects; diffractaic acid shows analgesic-antipyretic [ 23 ], hepatoprotective [ 30 ], antimycobacterial [ 31 ], cytotoxic, and anti-proliferative action [ 32 ]. Depsidone’s representatives (norstictic, connorstictic, stictic, salazinic, and lobaric acid) have proven antioxidant, antimicrobial, and antitumor properties [ 33 ]. It has been reported that major U. barbata secondary metabolites have antioxidant potential [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, from the depsides group, atranorin shows antimicrobial, anti-proliferative, cytoprotective, anti-inflammatory, and antioxidant activities [ 26 ]; lecanoric acid has antimicrobial [ 27 ], anti-proliferative [ 28 ], and antioxidant [ 29 ] effects; diffractaic acid shows analgesic-antipyretic [ 23 ], hepatoprotective [ 30 ], antimycobacterial [ 31 ], cytotoxic, and anti-proliferative action [ 32 ]. Depsidone’s representatives (norstictic, connorstictic, stictic, salazinic, and lobaric acid) have proven antioxidant, antimicrobial, and antitumor properties [ 33 ]. It has been reported that major U. barbata secondary metabolites have antioxidant potential [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lichens produce a wide variety of secondary metabolites with most being synthesized by the mycobiont [27]. Approximately 1050 secondary compounds have been identified [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated protocetraric acid and salazinic acid (Figure 1), two compounds belonging to the class of depsidones, some of the most abundant lichen secondary metabolites [30]. Depsidones are biosynthesized from depsides, which are themselves formed by the condensation of two or more hydroxybenzoic acids where the carboxyl group of one molecule is esterified with a phenolic hydroxyl group of a second molecule [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…crispiformis [ 89 ]. Among these metabolites, usnic, fumarprotocetraric, protocetraric, and protolichesterinic acids stand out for their potential biological applications [ 13 , 90 , 91 , 92 ].…”
Section: Phytochemistrymentioning
confidence: 99%